İstanbul'da Özel Bir Okulda Görev Yapan Eğitim Yöneticilerinin İnovasyon Kavramı Hakkındaki Görüş ve Önerileri - Sağlam, Özge (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Eğitim Bilimleri Anabilim Dalı / Eğitim Yönetimi ve Planlaması Bilim Dalı, 2018)
Gelişen yüzyılda artık herkesin olmazsa olmazı, teknolojik aletler ve onların kullanımıdır. Günlük hayatta akıllı telefonların kullanımı, bilgisayarlar, tabletler gibi birçok teknolojik alet zamanımızın büyük bir kısmını işgal etmektedir. Özellikle küçük yaşlardaki çocuklar teknolojinin içine doğduklarından her türlü teknolojik aleti rahatlıkla kullanabiliyor, bilgiye anında ulaşıyor ve eğitimleri online almak istiyorlar. Tüm bu gelişmeler ve yeni neslin ihtiyaçları da çeşitli alanlarda yapılan yenilik ve değişimi beraberinde getiriyor. Bu araştırmanın amacı, özel bir okul yöneticilerinin eğitimde inovasyon ile ilgili görüş ve önerilerini incelemektir. Nitel araştırma desenlerinden durum (vaka) analizinin kullanıldığı bu çalışma, İstanbul' da bulunan iki kampüse sahip ve bünyesinde inovasyon merkezleri bulunduran özel bir okulda görev yapan okul yöneticileri ile gerçekleştirilmiştir. Çalışmaya bu özel okulun bir kampüsünden, 3 okul yöneticisi, diğer kampüsünden ise 2 okul yöneticisi katılmıştır. Kavramsal çerçeve doğrultusunda araştırmanın veri toplama aracı olan yarı yapılandırılmış görüşme formu oluşturulmuştur. Araştırma amacıyla yapılan görüşmeler sonucunda, ilk bakışta yöneticilerin inovasyon kavramı hakkında bir farkındalığa sahip oldukları ve bu farkındalığın tüm kuruma yayılması adına yapmış oldukları çalışmalar göze çarpmaktadır. Fakat araştırma sorularına verilen cevaplar incelendiğinde, kurumun henüz inovasyonu benimseyemediği, kurulan inovasyon merkezi içerisinde henüz inovatif çalışmaların sergilenmediği ve daha çok bu merkezin teknolojik araçların kullanımı için hazırlanmış bir derslik gibi kullanıldığı gözlenmiştir. Fakat yöneticilerin araştırma sorularına vermiş oldukları cevaplara bakıldığında henüz 2016 yılında kurulan bu merkezin gelişmesi ve üretim yapılması için gereken tüm desteğinin sağlandığı kanısına varılmıştır. Dolayısıyla henüz iki yıldır hizmet veren bu merkezin gelişerek değişeceğine hiç şüphe yoktur.

The technological tools and their use become irreplaceable in the developing world. To use of smart phones, computers and tablets as many of other technological devices occupy our time in the everyday life. Especially children grow with technology since their early ages. As a consequent of interrelations between them lead children to use devices easily, to reach data instantly and to intend participating online educational courses. Technological developments and needs of new generation cause to make new innovations and changes in variety of fields. The aim of this research is to examine opinions and recommendations of a private school administrator about innovations in education. This study made with the situation analysis which is one pattern of the qualitative research. Furthermore, it became realized with school administrators in the private school with two campuses and the innovation center in Istanbul. Three administrator participated to this research, one is from one campus and other two administrator from other campus. In the conceptual phase, the form of semi-structured interview was constituted as the data collection tool. The technological tools and their use become irreplaceable in the developing world. To use of smart phones, computers and tablets as many of other technological devices occupy our time in the everyday life. Especially children grow with technology since their early ages. As a consequent of interrelations between them lead children to use devices easily, to reach data instantly and to intend participating online educational courses. Technological developments and needs of new generation cause to make new innovations and changes in variety of fields. The aim of this research is to examine opinions and recommendations of a private school administrator about innovations in education. This study made with the situation analysis which is one pattern of the qualitative research. Furthermore, it became realized with school administrators in the private school with two campuses and the innovation center in Istanbul. Five administrator participated to this research, three are from one campus and other two administrator from other campus. In the conceptual phase, the form of semi-structured interview was constituted as the data collection tool. According to the result of made interviews for the research, studies draw to attention at first; administrators' awareness to the notion of ' innovation' and their works and contributions to spread these innovations to their institution. Results of the research register that the institution can not adapt to innovations, not carry on innovative workings in the innovation center. The use of this innovation center is observed as a classroom designed for technological devices. Also administrators' answers indicate necessary supports and requirements were provided for institutional developments and production in 2016. As a consequence, this innovation center, offering service just two years, is promising for growingly changes.
Private School Administrators Views and Suggestions Oninnovation School Concept at a Private School in İstanbul